Pengaruh Iklan dan Promosi Penjualan terhadap Kesadaran Merek Lemari Es - Desra Ayu Rahmadani; Mukran Roni (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
This study aims to determine the effect of advertising and sales promotion on refrigerator brand awareness. This research is a quantitative study with the method used in sampling, namely the quota sampling technique by accidental sampling with a sample of 50 respondents who are housewives who live in the Kel. 30 Ilir Kec. Ilir Barat II Palembang City. Partial testing of advertising variables has a positive and significant influence on brand awareness. It states that refrigerator advertising is able to increase brand awareness. Partial testing of sales promotion variables has a positive and significant influence on brand awareness. It states that sales promotions carried out by the refrigerator brand are able to increase brand awareness. Simultaneously the advertising and sales promotion variables on brand awareness significantly affected the value of the determination coefficient of 0.636 which means 63.6% variations in brand awareness variables are explained by advertising and sales promotion variables while the remaining 36.4% are explained by variables not examined or included in the regression model